TO THE QUESTION OF THE CHARACTERISTICS OF THE NEUROLOGICAL STATUS IN CHILDREN AT DIFFERENT STAGES OF HIV INFECTION - Dilnoza F. Mirzaeva, Shaanvar Sh. Shamansurov (International Journal of Advanced Science and Technology, 2020)
The problem of pediatric HIV infection remains relevant in medical and social terms. The magnitude of the disease, the lack of specific prophylaxis, expensive treatment give the right to attribute HIV / AIDS to the world's most important problems. Despite of the significant progress in studying various aspects of HIV / AIDS management, morbidity and mortality is remain high. This work analyzed the results of a survey of children at various stages of HIV infection. 110 children from 8 months to 10 years old with different neurological status were studied. It was established that damage for the nervous system is a pathognomonic manifestation of HIV infection in childhood and a characteristic increase in neurological manifestations as immunodeficiency progress.